STUDY OF THE CORROSION BEHAVIOR OF Co-W COATINGS IN VARIOUS ENVIRONMENTS - Silkin, Sergey A.; Kusmanov, Sergey A.; Perkov, Alexander S.; Parfenyuk, Vladimir I. (ChemChemTech, 2024)
Corrosion behavior of So-W coatings obtained from citrate electrolyte (with W content in the coating of about 24 att. %) in the following corrosive environments was studied by the methods of electrochemical impedance and polarization measurements: 0.6M sodium chloride (3.5 mass%), 0.1 M sodium sulfate (Na2SO4), 1 M hydrochloric acid (HCl) and 0.5M sulfuric acid (H2SO4). As a comparison, JIS-SK5 steel, which acts as a substrate during deposition, was taken. It is shown that the corrosion current of Co-W coatings in three corrosive media (sodium chloride, hydrochloric acid and sodium sulfate) is close to 20±3 µA/cm2. When exposed to acidic environments, the corrosion potential of Co-W coatings shifts to the anodic region reaching values of -0.260 V, and in neutral environments (chloride and sulfate) it reaches significantly higher values of -0.76 V. The high passivating ability of the Co-W coating in used acids is demonstrated, where the corrosion current is more than 100 times (in the case of sulfuric acid) and 17 times (in the case of hydrochloric acid) less than that of the SK-5 steel substrate. The maximum polarization resistance of So-W coatings is observed in sodium chloride and sulfuric acid environments and takes a maximum value of ~36000 Ohm·cm2, and the minimum value of this coating shows ~3500 Ohm·cm2 in hydrochloric acid environment. For citation: Silkin S.A., Kusmanov S.A., Perkov A.S., Parfenyuk V.I. Study of the corrosion behavior of Co-W coatings in various environments. ChemChemTech [Izv. Vyssh. Uchebn. Zaved. Khim. Khim. Tekhnol.]. 2024. V. 67. N 11. P. 69-78. DOI: 10.6060/ivkkt.20246711. 7033.